The Influence of Consumer Product Knowledge, Trust and Risk Perception on Purchase Intention of Shopee Consumers - Nadila Desyanata; Alimuddin Rizal Rivai (SEAN Institute, 2024)
The aim of this research is to analyze the influence of consumer product knowledge, trust and risk perception on purchase intention among Shopee consumers. It is hoped that the results of this research can be used as input or reference material for further research or as a comparison for conducting research in the future.This research uses quantitative research. The population used in this research is all Shopee consumers. The sample was 100 respondents, this research used purposive sampling. The analysis used is validity test, reliability test, multiple linear regression, F test,Coefficient of Determination (R2) and t test.The results of this research show that purchase intention is influenced byconsumer product knowledge, trust, risk perception. The most dominant variable influencing purchase intention is consumer product knowledge. Meanwhile, the variable with the least influence is the risk perception variable.